2017
DOI: 10.1038/nature23314
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the protein-conducting ERAD channel Hrd1 in complex with Hrd3

Abstract: Misfolded endoplasmic reticulum (ER) proteins are retro-translocated through the membrane into the cytosol, where they are poly-ubiquitinated, extracted from the ER membrane, and degraded by the proteasome 1–4, a pathway termed ER-associated protein degradation (ERAD). Proteins with misfolded domains in the ER lumen or membrane are discarded through the ERAD-L and –M pathways, respectively. In S. cerevisiae, both pathways require the ubiquitin ligase Hrd1, a multi-spanning membrane protein with a cytosolic RIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 52 publications
5
167
0
Order By: Relevance
“…128 The two core molecules of the ERAD machinery are the partner proteins HRD1 and SEL1/HRD3, which are conserved even in yeast. 129 The polytopic HRD1 membrane protein functions in both retrotranslocation and as an E3 ubiquitin ligase, whereas the single membrane–spanning SEL1 physically associates with HRD1 and is required for HRD1 protein stability, while also helping to present ERAD substrates to HRD1; many other ancillary proteins interact with the core complex, and these topics are reviewed in detail elsewhere. 130 The ERAD core complex is upregulated by the ER stress response, 36,131 suggesting that one of its key functions is to help cells adapt to the ER load of misfolded proteins.…”
Section: Misfolded Proinsulin Clearancementioning
confidence: 99%
“…128 The two core molecules of the ERAD machinery are the partner proteins HRD1 and SEL1/HRD3, which are conserved even in yeast. 129 The polytopic HRD1 membrane protein functions in both retrotranslocation and as an E3 ubiquitin ligase, whereas the single membrane–spanning SEL1 physically associates with HRD1 and is required for HRD1 protein stability, while also helping to present ERAD substrates to HRD1; many other ancillary proteins interact with the core complex, and these topics are reviewed in detail elsewhere. 130 The ERAD core complex is upregulated by the ER stress response, 36,131 suggesting that one of its key functions is to help cells adapt to the ER load of misfolded proteins.…”
Section: Misfolded Proinsulin Clearancementioning
confidence: 99%
“…Among these strategies, the ERAD system directly recognizes misfolded proteins and mediates their degradation by proteasomes (Vembar & Brodsky, 2008;Strasser, 2018). Extensive studies of 3-HYDROXY-3-METHYLGLUTARYL (HMG)-COA REDUCTASE DEGRADATION (Hrd1) and DEGRADATION OF ALPHA2 (Doa10) pathways in yeast and mammals have shown that ERAD consists of four steps: (1) recognition of the cargo proteins by lectins or chaperones through Man 7 GlcNAc 2 N-glycans or the protein backbone; (2) retrotranslocation of the ER lumen or ER membrane cargo proteins to the cytoplasm via an ER membrane protein channelfor instance, observations of the structure of E3 ligase Hrd1 revealed that it forms a retro-translocation pore for the movement of misfolded proteins through the ER membrane in Saccharomyces cerevisiae (Schoebel et al, 2017); (3) ubiquitination of the substrate proteins by E1 (ubiquitin-activating enzyme), E2s (ubiquitin conjugating enzymes) and E3s (ubiquitin E3 ligases), three enzymes that are essential for protein ubiquitination in a cascade of catalytic ubiquitination reactions; and (4) degradation of ubiquitinated substrates through the 26S proteasome.…”
Section: Introductionmentioning
confidence: 99%
“…Hrd1p has also been reported as a possible retro-translocon channel due to the requirement of its oligomerization for the degradation of ER luminal misfolded proteins and its transmembrane domain, which interacts with substrates [43,44]. In a recent report, a cryo-electron microscopic study revealed that Hrd1p forms a retro-translocon channel for the movement of misfolded polypeptides through the ER membrane in collaboration with Hrd3p [51]. Further experimental evidence using mammalian HRD1 could show the evolutionary conservation regarding the retro-translocon channel.…”
Section: Er-associated Degradation (Erad)mentioning
confidence: 99%